Improving Science Learning Outcomes Human Body Tools Function Materials Through Picture Game Puzzles Class IV Semester 1 SD Negeri 1 Sindon Ngemplak Boyolali - Prakosa, Haryo (Universitas Sebelas Maret, 2022)
The purpose of this study was to get an overview of students' learning activities in science learning in Class IV SD Negeri 1 Sindon by using a puzzle game. The form of this research is classroom action research consisting of two cycles, each cycle consisting of four stages, namely planning, implementing, observing and reflecting. The research subjects were fourth grade students at SD Negeri 1 Sindon, Ngemplak District, with a total of 13 students.The sources of data used in this study were the results of formative tests cycle I and cycle II as well as field observation notes on the initial conditions, cycle I and cycle II as well as class observations. Based on the research results obtained by applying the puzzle game method that in cycle I there were students who had scores below 70 with the lowest score 50 and the highest 85, an average of 68.46. Student learning outcomes in cycle II, namely student scores on test results at the end of cycle II, it turns out that out of 7 students, only 1 student (3.85%) scored below 70, the lowest score was 65 and the highest was 100 with an average score of 79.Based on the learning results obtained that in cycle II student learning outcomes increased from cycle I. based on the research results obtained, it can be concluded that through picture game puzzles can improve science learning outcomes.